Expert validation of a research culture assessment tool for secondary schools - Wan Mohd Khairi, Wan Ibrahim; Suhaidah, Hussain; Azim Azuan, Osman (Human Resource Management Academic Research Society, 2024)
The development of a strong research culture in secondary schools is critical for enhancing teaching practices and encouraging student learning. However, there is a lack of reliable tools specifically designed to assess the level of research culture within these institutions. This study aims to develop and validate a research culture assessment tool customized for secondary schools in Malaysia. A survey questionnaire was created to measure core indicators of research culture and was evaluated by a panel of ten experts for content validity. The Content Validity Index (CVI) and Inter-Rater Agreement (IRA) were used to analyze the experts' ratings. Items with an I-CVI score of 0.80 or higher were retained, while items scoring lower were modified or removed. The findings showed robust content validity across most items, indicating that the tool accurately reflects the relevant dimensions of research culture in secondary schools. However, some items required revision based on expert feedback. Further statistical tests, such as construct validity and reliability analysis, are recommended to ensure the tool’s robustness across diverse educational settings. This validated tool is expected to play a crucial role in guiding future efforts to cultivate research culture in schools, contributing to the professional development of teachers and the improvement of student outcomes.